Early repolarization in adolescent athletes: A gender comparison of ECG and echocardiographic characteristics. (15th September 2022) - Vecchiato, Marco; Baioccato, Veronica; Adami, Paolo Emilio; Quinto, Giulia; Foccardi, Giulia; Slanzi, Giulio; Battista, Francesca; Neunhaeuserer, Daniel; Ermolao, Andrea
Abstract : Background: The early repolarization pattern (ERp) is an electrocardiographic finding previously associated with arrhythmic risk in adults. The purpose of this study is to evaluate the prevalence and characteristics of ERp in a group of adolescent athletes according to gender. Furthermore, potential associations with clinical, electrocardiographic, and echocardiographic parameters are explored. Methods: In this cross‐sectional study young athletes (age < 18 years) were consecutively enrolled during the annual pre‐participation evaluation, undergoing also transthoracic echocardiography assessment from January 2015 to March 2020. Results: The prevalence of ERp was 27% in the whole population. Athletes with ERp were more frequently men practicing endurance sports. Women with ERp showed lower heart rate at rest, greater posterior, and relative ventricular wall thickness than those without ERp. Men with ERp presented higher systolic blood pressure at peak exercise, greater septal wall thickness, and indexed left ventricular mass than those without ERp. Both genders with ERp showed increased QRS voltage and narrower QRS duration. The ERp phenotype in men was more frequently notched with higher amplitude and ascending ST segment. Women's ERp presented more frequently a slurred morphology, especially in the inferior leads, and horizontal ST slope. No differences emerged in the occurrence of arrhythmias at rest and during maximal exercise test between groups, even considering higher risk phenotypes. Conclusions: ERp is an ECG finding compatible with normal cardiac adaptations to training in young athletes. ERp demonstrated gender differences regarding phenotypes previously associated with increased cardiovascular risk, not showing any differences in arrhythmias during maximal exercise test.